2016
DOI: 10.1080/14756366.2016.1178247
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of biological activities and multicomponent pattern of two wild Turkish species: Asphodeline anatolica and Potentilla speciosa

Abstract: The multicomponent pattern and biological characterization of plant material are essential for pharmaceutical field, in the food supplements quality control procedures and to all plant-based products. These nutrients often show valuable effects related to their consumption due to the occurrence of secondary metabolites that show useful properties on health. In this framework, researches performed on this topic play a central role for human health and drug development process. The aim of this study was to compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(29 citation statements)
references
References 40 publications
4
23
0
2
Order By: Relevance
“…The samples injection volume was 25 mL, column temperature at 30 C and flow rate at 1.5 mL/min. The programed solvent used began with a linear gradient held at 95% A for 3 min, decreasing to 80% A at 10 min, 60% A at 20 min, 20% A at 30 min and finally 95% A at 50 min 5,25 .…”
Section: Determination Of Phenolic Profilementioning
confidence: 99%
“…The samples injection volume was 25 mL, column temperature at 30 C and flow rate at 1.5 mL/min. The programed solvent used began with a linear gradient held at 95% A for 3 min, decreasing to 80% A at 10 min, 60% A at 20 min, 20% A at 30 min and finally 95% A at 50 min 5,25 .…”
Section: Determination Of Phenolic Profilementioning
confidence: 99%
“…Four antiinflammatory assays were performed viz: dieneconjugate, -glucuronidase, hyaluronidase, and lipoxidase inhibition (Nile and Khobragade, 2011). The enzyme inhibition activity checked against -amylase, -glucosidase, acetylcholinesterase, and butyrylcholinesterase as per methods described previously (Zengin et al, 2016).…”
Section: Antioxidant Anti-inflammatory and Enzyme Inhibitory Activitmentioning
confidence: 99%
“…The lowest reducing power activity was observed for ethyl acetate extracts. The reducing power activity of the methanol extract of P. speciosa root (FRAP: 133.35 and CUPRAC: 189.24 mg TE/g) was significantly lower than results obtained for aerial parts of P. speciosa (FRAP: 191.53 and CUPRAC: 264.62 mg TE/g) (Zengin et al, 2016). Liu et al (2016) reported that the FRAP values of P. fruticosa collected from eight locations ranged from 112.24 to 436.58 μmol TE/g.…”
Section: Resultsmentioning
confidence: 79%
“…Compact (LabService, Anzola dell’Emilia, Italy). Gradient elution was performed using the mobile phase water-acetonitrile (93:7, v/v, 3% acetic acid) (Zengin et al, 2016). The UV/Vis acquisition wavelength was set in the range of 200–500 nm.…”
Section: Methodsmentioning
confidence: 99%